2014
DOI: 10.5888/pcd11.130390
|View full text |Cite
|
Sign up to set email alerts
|

Defining Powerhouse Fruits and Vegetables: A Nutrient Density Approach

Abstract: National nutrition guidelines emphasize consumption of powerhouse fruits and vegetables (PFV), foods most strongly associated with reduced chronic disease risk; yet efforts to define PFV are lacking. This study developed and validated a classification scheme defining PFV as foods providing, on average, 10% or more daily value per 100 kcal of 17 qualifying nutrients. Of 47 foods studied, 41 satisfied the powerhouse criterion and were more nutrient-dense than were non-PFV, providing preliminary evidence of the v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
48
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(49 citation statements)
references
References 6 publications
(13 reference statements)
0
48
1
Order By: Relevance
“…Collard (B. oleracea), classified in the kale "acephala" group [4], and kale (B. oleracea or B. napus) are one of the frequently consumed leafy vegetables all around the world. A study from Centers for Disease Control and Prevention reported collard and kale being ranked at 10th and 15th place of "powerhouse" fruits and vegetables [5].…”
Section: Introductionmentioning
confidence: 99%
“…Collard (B. oleracea), classified in the kale "acephala" group [4], and kale (B. oleracea or B. napus) are one of the frequently consumed leafy vegetables all around the world. A study from Centers for Disease Control and Prevention reported collard and kale being ranked at 10th and 15th place of "powerhouse" fruits and vegetables [5].…”
Section: Introductionmentioning
confidence: 99%
“…Vegetables in the cruciferous (such as Chinese cabbage, broccoli) and green leafy (e.g. spinach) groups have significantly high nutrient density scores, and therefore, both Chinese cabbage and spinach today feature among the top 10 PFV . The present study suggests that consumers may be more responsive to nutrient labelling rather than the specific health benefits arising from nutrient consumption.…”
Section: Discussionmentioning
confidence: 68%
“…spinach) groups have significantly high nutrient density scores, and therefore, both Chinese cabbage and spinach today feature among the top 10 PFV. 34 The present study suggests that consumers may be more responsive to nutrient labelling rather than the specific health benefits arising from nutrient consumption. This finding is not surprising given the focus on nutrition education programmes among government and health promotion agencies.…”
Section: Vegetable Free Elicitation (% Respondents) Consumer Ranking mentioning
confidence: 72%
See 2 more Smart Citations